Political Science : theory and practice - Mazher Ul Haque (Lahore: Bookland Publishers, 2004)
"Political Science: Theory and Practice" by Mazher Ul Haque provides a comprehensive exploration of the foundational concepts, theories, institutions, and real-world applications of political science. The book bridges classical political theory and contemporary political practices, offering students and readers an in-depth understanding of how political systems function both in theory and in the real world. It examines key political ideologies, governance structures, constitutional frameworks, and the functioning of political institutions such as the legislature, executive, judiciary, political parties, and pressure groups. The author also addresses pressing global issues such as democracy, human rights, political development, and international relations. Written in a clear and accessible style, this book serves as a valuable resource for students, educators, and anyone interested in understanding the dynamics of politics and governance.
DC010725
Social Sciences
In English
Keywords: Political science -- Theory and practice